The scrapbooker's creativity kit prompts and ideas to jump start your layouts - Hellmuth, Claudine 1974- (Memory Makers Books, 2009)
The Scrapbooker's Creativity Kit" provides a unique and exciting way for scrapbookers to get the inspiration they have been seeking. Inside the kit, readers will find inspiration cards sorted by colour and word. These cards are starting points for creating layouts that spur the reader to think beyond the obvious.Included are selections of artwork from Claudine and her group of contributing artists in which each piece was created using the same combination of colours and words. The multiple interpretations show readers how the cards can be mixed and matched to create numerous layouts.